ANALISIS PERAWATAN PADA KOMPONEN MESIN DEGREASER DI PT X - Ferry Budhi Susetyo; Ragil Sukarno; Khulaifiyah (Jurnal Konversi Energi dan Manufaktur, 2022)
In maintenance activities at PT. X, which is engaged in the sports equipment industry, is not doing well. So that it can reduce the targeted production results in a day. For that, it is necessary to know the critical components in the degreaser machine that cause the machine to stop. The first thing to do in this research is to select the critical components using a Pareto diagram. Based on the Pareto diagram, it was found that the chain component is a critical component with the amount of damage 4 times (11.76%). The Weibull distribution with two parameters is used to determine the time between failures so that it can be determined when to replace critical components to minimize the damage that occurs. From the calculation of the chain components, the value of the Weibull parameter is obtained from the repair time = 1.101; = 5,331 and the value of MTTR = 1,003 hours. While the value of the Weibull parameter using the operational time is = 1686.458; = 2,205 and MTTF value = 1584.748 hours. From the calculation, the reliability level of the chain components is 90% for 605.438 hours and 80% for 863.348 hours.